IMPLEMENTASI PROGRAM KELUARGA BERENCANA METODE KONTRASEPSI JANGKA PANJANG DI UPT PPKB KECAMATAN INDRAMAYU - Rahmawati Rahmawati; Idham Latif; Muhamad Fauzi (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Based on the results of the population census conducted by the BPS in 2020, the population of Indonesia reached 270,203,917 people. Therefore, the implementation of the family planning program aims to meet the demand for family planning services and control the birth rate. However, in program implementation, MKJP's achievements in Indramayu Regency in the last 4 years (2018-2021) show relatively stable results. This study aims to determine the implementation of the Long Term Contraception Method (MKJP) program at the UPT for Population Control and Family Planning, Indramayu District. The research method uses qualitative methods. The informants were 6 program implementers at the district and sub-district levels of Indramayu. Data was collected by means of in-depth interviews. The results showed on the input variables that there was no training held by the regions, there was no special promoter staff, the availability of funds was not sufficient, especially for BKR, BKB, and BKL activities and the availability of logistical facilities and infrastructure was sufficient. The process variable shows that counseling is carried out at any time by visiting the WUS crowd in Elementary Schools, PAUD, Jamiaan, and Posyandu. PLKB conducts small groups targeting WUS, Catin, and youth. The implementation of MOP and MOW has not been maximized. The output variable shows that MKJP's achievement has not yet reached the target, family planning acceptors reach more women. The results of the study concluded that the implementation was less than optimal.